A systematic review of the effects of psychosocial interventions on social functioning for middle‐aged and older‐aged adults with severe mental illness. (13th February 2020) - Smart, Emily L.; Brown, Laura; Palmier‐Claus, Jasper; Raphael, Jessica; Berry, Katherine
Abstract : Objectives: The number of older adults with severe mental health problems such as schizophrenia is likely to double in the next 20 years. The needs of this patient group change across the life course, but difficulties with social functioning persist into older age. Poorer social functioning is associated with poorer outcomes and has been identified as a priority for intervention by patients themselves. This paper systematically reviews studies examining the effectiveness of psychosocial interventions on social functioning for people with severe mental health problems in later life. Methods: A systematic review of peer‐reviewed journal articles was conducted and databases were searched from inception to December 2017. The review was limited to psychosocial interventions, for mid to older aged adults (≥40 years of age) with severe mental illness that included a validated measure of social functioning. Results: Fifteen studies (17 papers) met inclusion criteria. There was evidence to support skills training interventions that primarily focused on social skills training or integrated mental and physical health interventions. There was not sufficient evidence to recommend any other interventions. Conclusions: The results highlight the limited nature of interventions designed specifically for older people with severe mental health problems that target social functioning and the need for more robust, large‐scale studies in the area. Current evidence suggests that cognitive behaviour therapy can be effective in targeting social functioning in younger age groups, but, as yet, there is insufficient evidence to recommend this intervention for an older population.